Late Holocene Precipitation Fluctuations in South America Triggered by Variability of the North Atlantic Overturning Circulation. Issue 9 (14th September 2021) - Bahr, A.; Kaboth‐Bahr, S.; Jaeschke, A.; Chiessi, C.; Cruz, F.; Carvalho, L.; Rethemeyer, J.; Schefuß, E.; Geppert, P.; Albuquerque, A. L.; Pross, J.; Friedrich, O.
Abstract: Historic droughts document the strong spatio‐temporal variability of the South American Monsoon System, which currently provides more than two thirds of the rainfall in tropical South America. The drivers of this variability have remained not well understood due to the lack of continuous, high‐resolution paleorecords, especially from the more arid regions of tropical South America. Here we present a novel record of moisture availability across eastern South America for the past ∼5, 000 years from a sediment core retrieved off eastern Brazil. We document distinct decadal‐ to millennial‐scale spatial shifts of major atmospheric convection centers that caused increasingly pronounced droughts in eastern South America over the past ∼2, 000 years. These fluctuations were triggered by climate anomalies in the high northern latitudes and propagated into equatorial latitudes via fluctuations in North Atlantic Overturning Circulation strength. As global warming is expected to decrease oceanic overturning due to enhanced meltwater input into the North Atlantic while at the same time reducing precipitation over eastern South America, an increasing risk for long‐lasting droughts can be expected for this region, posing severe socio‐economic challenges. Key Points: Marine record documents decadal‐ to millennial‐scale fluctuations of monsoonal rainfall in eastern South America during the past 5, 000 years Precipitation variability was caused by antiphased shifts of South Atlantic Convergence Zone and South American Low‐Level Jet Changes in oceanic overturning strength mediate transfer of high‐northern‐latitude climate disturbances into southern hemisphere tropics